INTEGRITAS PELAYANAN PUBLIK DALAM PERIZINAN PEMANFAATAN AIR BAWAH TANAH DI DKI JAKARTA - Ary Wahyono; Dede Wardiat (Jurnal Masyarakat dan Budaya, 2012)
The failure of government to provide water supplies for industries and households in DKI Jakarata and its surrounding will exacerbates the condition of water resources in Jabodetabek. Therefore, gratification in ground water services occurs in the permit process, especially on the stage in obtaining technical recommendation which is proposed in order to conduct drilling to decide the the location of ground water and subsequently recommendation letter will be issued as consideration to grant permit for taking ground water (SIPAT). Gratification can be occurred in law enforcement process. Since the enactment of the law no 7/2004 on water resources, violence is not categorized as administrative sanction only but also criminal. Based on this law the police can arrest the offenders. Gratification practice occurs when there is an effort to shifting from criminal sanction to non criminal. The others thing related to public services is the enactment of new taxation law comes into force 2011 where previously tax manage by provincial level now transfer to city/regent level. With this enactment there is probability to eliminate the fundamental function of ground water as temporary replacement of surface water. Ground water is seen as source to increase local revenue. This trend is predicted gives significant impact to the condition of ground water in the future.